HUBUNGAN PREMENSTRUAL SYNDROME DENGAN KUALITAS TIDUR SISWI MTs. ZAINUL HASAN - Aprilia Kusuma Wardani; Melati Puspita Sari; Asri Iman Sari; Trisna Pangestuning Tyas (Poltekkes Kemenkes Maluku, 2026)
Background: Premenstrual Syndrome (PMS) is a set of physical, emotional, and behavioral symptoms that appear before menstruation and usually subside afterward. Hormonal imbalances of estrogen and progesterone are among the triggering factors for PMS symptoms. These imbalances can affect the central nervous system through a decrease in serotonin and melatonin levels, which play an important role in regulating mood and the sleep cycle. As a result, many women experience sleep disturbances before menstruation. At MTs. Zainul Hasan Balung, 48 out of 90 students (53.3%) experience PMS.Objective: To analyze the relationship between the occurrence of premenstrual syndrome and sleep quality among female students at MTs. Zainul Hasan. Methods: This research is a quantitative analytic study with data collected observationally. The sample consisted of 48 female students at MTs. Zainul Hasan, selected using a purposive sampling technique. Data were analyzed using the Chi-square test. Results: The study found that 20 students (41.7%) experienced mild PMS symptoms, 23 students (47.9%) experienced moderate PMS symptoms, and 5 students (10.4%) experienced severe PMS symptoms. In terms of sleep quality, 28 students (58.3%) had poor sleep quality, while 20 students (41.7%) had good sleep quality. Data analysis using the Chi-square test yielded a p-value of 0.000 (<0.05) and a correlation coefficient of 0.554. Conclusion: There is a moderate association between premenstrual syndrome and sleep quality among female students at MTs. Zainul Hasan. Recommendation: Advice for female students to take steps to relieve PMS symptoms, such as regular exercise, which will improve the quality of sleep.